Sikkim State Draft Annual Plan 1986-87 - Planning Commission (Planning Commission, 1986)
Inflationary trend and also due to the fact that commitments on account of certain unforeseen items has been unavoidable. Among the sectors needing special consideration, mention may be made of power development for which substantial additional resources are inevitable if any appreciable augmentation in the generation projects is to be achieved. The extensive programme envisaged under the Rural Electrification scheme will be meaningless unless the supply of power for this purpose is properly synchronised though improvement of the overall generation capacity.
Planning and Development Department, Government of Sikkim